Quality eLearning: An instructional design model for developing pedagogically effective online learning in higher education - Siragusa, Lou (AARE Inc, 2007)
As online learning (or eLearning) is integrated into ever-growing numbers of university courses, there is a need for practical guidelines and recommendations to facilitate the development and delivery of pedagogically effective eLearning environments. A recent study by Siragusa (2005) examined factors which make for effective instructional design principles and learning strategies for higher education students studying with these environments. Surveys were administered to students and lecturers in Western Australian universities revealing numerous areas of students' eLearning experiences which they had perceived as being successful and those needing improvements. This paper presents a model that was developed from the study's survey findings, which lecturers and instructional designers may use to design, develop, evaluate and refine their eLearning environments in higher education. The model is accompanied with recommendations that accommodate the varying pedagogical needs of learners as well as varying modes of course delivery. For each recommendation, a pedagogical dimension is presented to illustrate the varying pedagogical needs and instructional requirements. The dimensions are utilised in a similar manner to Reeves and Reeves' (1997) pedagogical dimensions and highlight the decisions which need to be made during the instructional analysis, design, delivery and evaluation phases for the implementation of pedagogically effective eLearning environments.